Undescended Testes in Children: Clinicopathological Study of 32 Cases (TAJ: Journal of Teachers Association, 2018)
Objective: To study the presentation, management, histopathological findings and outcome of undescended testes in children. Method: It was a prospective study done in Rajshahi Medical College Hospital and also private clinic in Rajshahi Metropolitan City during the period of 1st December, 2007 to June, 2010. Thirty two children aged 4 months to 13 years with 40 undescended testes were selected in this study. Interventions like Orchidopexy, orchidectomy, herniotomy were done.Results: The age at surgery was four months to 13 years (mean 5.25 + 0.61 SE years). Nine (28.13%) had corrected before two years, twenty three (71.87%) after two years. Twenty four testes (60%) were palpable and sixteen (40%) were non-palpable, none of then cases was diagnosed at birth. Ultrasonography was performed in all cases. Evaluation was done by clinical, sonological, pre-operation and histopathological findings, Laparoscopy was done in one case. The condition was unilateral in 24(75%) and bilateral in Eight (25%). Forty percent of the testes were in the inguinal canal, 34% at the external ring and 10% at the internal ring and 16% in the abdomen. Fifteen (46.87%) testes were macroscopically smaller in size, four (10%) testes were atrophic (all were canalicular), one was tumour. Orchidopexy was performed in for 35 undescended testes and orchidectomy for five. Scrotal haematoma developed in 2 cases. Histopathological finding showed no spermatogonia in 25 (78.12%), among then 23 were above 2 years, 2 were below 2 years. Follow-up period were 6 months to 18 months, no atrophy/retraction was observed.TAJ 2017; 30(2): 26-31